Community access to primary care is an important geographic disparity among ovarian cancer patients undergoing cytoreductive surgery - Abigail S. Zamorano; Angela L. Mazul; Christine Marx; Mary M. Mullen; Molly Greenwade; L. Stewart Massad; Carolyn K. McCourt; Andrea R. Hagemann; Premal H. Thaker; Katherine C. Fuh; Matthew A. Powell; David G. Mutch; et al. (Elsevier, 2022)
Objective: Given the importance of understanding neighborhood context and geographic access to care on individual health outcomes, we sought to investigate the association of community primary care (PC) access on postoperative outcomes and survival in ovarian cancer patients. Methods: This was a retrospective cohort study of Stage III-IV ovarian cancer patients who underwent surgery at a single academic, tertiary care hospital between 2012 and 2015. PC access was determined using a Health Resources and Services Administration designation. Outcomes included 30-day surgical and medical complications, extended hospital stay, ICU admission, hospital readmission, progression-free and overall survival. Descriptive statistics and chi-squared analyses were used to analyze differences between patients from PC-shortage vs not PC-shortage areas. Results: Among 217 ovarian cancer patients, 54.4 % lived in PC-shortage areas. They were more likely to have Medicaid or no insurance and live in rural areas with higher poverty rates, significantly further from the treating cancer center and its affiliated hospital. Nevertheless, 49.2 % of patients from PC-shortage areas lived in urban communities. Residing in a PC-shortage area was not associated with increased surgical or medical complications, ICU admission, or hospital readmission, but was linked to more frequent prolonged hospitalization (26.3 % vs 14.1 %, p = 0.04). PC-shortage did not impact progression-free or overall survival. Conclusions: Patients from PC-shortage areas may require longer inpatient perioperative care in order to achieve the same 30-day postoperative outcomes as patients who live in non-PC shortage areas. Community access to PC is a critical factor to better understanding and reducing disparities among ovarian cancer patients.